Reconnecting with nature: Developing urban spaces in the age of climate change [version 1; peer review: 2 approved] - Steffen Lehmann (Emerald Publishing, 2019)
Climate change is occurring around us and impacting on our daily lives, meaning that we have to deal with our cities in a different way. There is also increasing awareness of the need for daily contact with green spaces and the natural environment in order to live a happy, productive and meaningful life. This reflective essay tells the narrative of how urbanisation has been disconnecting humans from nature. Non-sustainable, non-resilient patterns of urbanisation, along with the neglect of inner-city areas, have resulted in fragmentation and urban decline, led to a loss of biodiversity, and caused the deterioration of ecosystems and their services. Urban regeneration projects allow us to 'repair' and restore some of this damage whilst enhancing urban resilience. Connecting existing and enhanced ecosystems, and re-establishing ecosystems both within cities and at the peri-urban fringe is vital for strengthening ecosystem resilience and building adaptive capacity for coping with the effects of climate change. Cities worldwide need to look for suitable solutions to increase the resilience of their urban spaces in the face of climate change. This essay explores how this can be achieved through the integration of nature-based solutions, the re-greening of neighbourhoods and by correctly attributing value to natural capital. Transforming existing cities and neighbourhoods in this way will enable ecosystems to contribute their services towards healthier and more liveable cities.